Life abroad Effects, problems and ways of coping of selected Overseas Filipina Workers (OFW). - Alura, Sherna C.; Daban, Virginia C. (Tacloban City Sherna C. Alura, 2009)
This paper is a study on the effects, problems and ways of coping of Overseas Filipina Workers. It aimed to find out particular effects of working abroad to the OFW herself, particular problems they have encountered and their ways of coping.
Eleven respondents participated in the study, purposively chosen from two different agencies: New Era Placement Agency and Mother's Way Agency. They compose exclusively by females, 29-49 years old with the mean age of 38.6. The data and pieces of information were gathered from them through a face to face interview.
After getting the data and information, the researchers used thematic analysis in interpreting the data. The researchers have found out that changes in skills and abilities, changes in psychological aspect and changes in attitude were the effects on the OFW itself.
The common problems they have encountered include: homesickness, problems with the employer, inggitan phenomenon, utangan System, culture, climate and language barrier, psychological problems, health problems, infidelity and misconceptions about OFW.
The researchers have found out 9 basic ways of coping which includes: focused on work, faith, maintaining constant communication with the family back home, conforms to the employer's attitudes, rules and regulations, socialization with other OFWs, recreational activities, optimistic view of dealing with their problems, advance insight about the possible job, country, employer to be dealt with and strong motivations.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban.
Keywords: Social Science